Incidence of delayed hair re-growth, pruritus, and urinary retention after epidural anaesthesia in dogs - Guerrero, K. S. Kalchofner; Guerrero, T. G.; Schweizer-Kölliker, M.; Ringer, S. K.; Hässig, M.; Bettschart-Wolfensberger, R. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: Delayed hair re-growth, pruritus and urinary retention are known complications after epidural anaesthesia in dogs. The aim of this study was to prospectively evaluate the effect of epidurally administered drugs on the occurrence of these complications in dogs. Material and methods: Ninety dogs were included in this study. Eighty client-owned dogs undergoing surgery were randomly assigned to one of three epidural treatment groups: either morphine and bupivacaine (MB), bupivacaine (B), or saline solution 0.9% (S) was administered epidurally to these patients. Ten dogs were only clipped in the lumbosacral area (C). Follow-up started 4 weeks after clipping and was performed every 4–5 weeks in cases of delayed hair regrowth or pruritus. Hair re-growth in the lumbosacral area was observed and compared to hair re-growth in the surgical field and the fentanyl patch area. Cytological analysis and a trichogram were performed if hair re-growth was delayed after 6 months. Time interval to first urination postoperatively was recorded (n = 80). Results: Hair regrowth was delayed in 11 dogs (12.2%; B: n = 7, S: n = 2, MB: n = 1, C: n = 1) with no differences between groups. Pruritus was evident in two dogs (2.2%; MB: n = 1, S: n = 1). After 6 months, hair had started to re-grow in all but one dog (B). After 10 months the coat of this dog had re-grown. Time to first urination did not differ between groups. Conclusion and clinical relevance: No direct correlation between the particular drugs injected epidurally and delayed hair re-growth, pruritus and urinary retention could be shown. Dog owners should be informed that hair re-growth after epidural anaesthesia could be markedly delayed.
Keywords: Canine; regional anaesthesia; morphine; bupivacaine; complications